PENERAPAN METODE SMART DALAM PEMILIHAN BIJI KOPI TERBAIK: Array (JiTEKH, 2020)
We can easily find coffee sellers today, both online and offline. Buying coffee in the form of beans will provide several benefits, such as a more durable aroma and usually of a higher quality. But unfortunately, now there are still many coffee buyers who don't know how to choose coffee beans with good quality. Therefore we need a system that can produce recommendations for selecting the best coffee beans based on determined criteria. This study uses the Decision Support System concept using the SMART method. The SMART method is a decision-making method to solve the problem of multi-objective choice among several criteria, so that later it can produce an effective and efficient analysis. Input criteria that become priority in the recommendation for selecting the best coffee beans are live insects (none requirements), foul smelling beans (non-existent requirements), moisture content, non-coffee dung content, defect values, and flavor (aroma). Of the 10 alternatives tested on this system, there were 5 types of coffee with a “Highly Recommended” rating, 2 types of coffee with a “Recommended” rating, and 3 types of coffee with a “Considered” rating